Advertising and marketing on the internet - Rutsohn, Phil; D.E. Visuals (Firm) (Florida : D.E. visuals, 2002)
Discusses the advantages and disadvantages of advertising and marketing on the Internet, common strategies used, and how to develop a web site.
DVD format
Keywords: Internet marketing; Internet advertising; Web sites -- Design